THE 100-YEAR LEGACY OF THE INSTITUTE OF MEDICAL CHEMISTRY - A CENTURY OF CHEMISTRY TEACHING AT THE FACULTY OF MEDICINE, UNIVERSITY OF BELGRADE - Gopčević, Kristina; Vujić, Vesna; Avramović, Nataša; Izrael Živković, Lidija; Medić, Ana; Đukić, Teodora; Lopandić, Zorana; Krstić, Danijela (Medical Research, 2024)
The Institute of Medical Chemistry “Prof. Dr. Petar Matavulj,” one of the oldest institutes of the Faculty of Medicine at the University of Belgrade, was founded in 1923. Recognizing the role of chemistry in understanding medical sciences, the founders of the Faculty of Medicine engaged leading authorities of that time in the field of chemistry: Sima Lozanić, Milivoje Lozanić, and Petar Matavulj, establishing a solid foundation for the quality education of future doctors. Over more than a century, the teachers and associates of the Institute have successfully addressed specific challenges in medical education, adapting to contemporary trends in science and education.